2015
DOI: 10.1007/s10040-015-1246-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of remotely sensed data for estimating recharge to an outcrop zone of the Guarani Aquifer System (South America)

Abstract: The Guarani Aquifer System (GAS) is the largest transboundary groundwater reservoir in South America, yet recharge in the GAS outcrop zones is one of the least known hydrological variables. The objective of this study was to assess the suitability of using remote sensing data in the water-budget equation for estimating recharge inter-annual patterns in a representative GAS outcropping area. Data were obtained from remotely sensed estimates of precipitation (P) and evapotranspiration (ET) using TRMM 3B42 V7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…On average, the baseflow (Qb/contributing area) represents ~25.0 ± 2.9% of the annual P , which agrees with the annual recharge rates (22% of P ), estimated by Lucas et al. () at the same basin. The runoff (Qs = Qt − Qb) in the OCB represents a small percentage (~2.0 ± 0.6%) of P ; hence, its contribution to Qt is almost negligible.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…On average, the baseflow (Qb/contributing area) represents ~25.0 ± 2.9% of the annual P , which agrees with the annual recharge rates (22% of P ), estimated by Lucas et al. () at the same basin. The runoff (Qs = Qt − Qb) in the OCB represents a small percentage (~2.0 ± 0.6%) of P ; hence, its contribution to Qt is almost negligible.…”
Section: Resultssupporting
confidence: 89%
“…; Lucas et al. ) and indicates that the aquifer in the OCB has an important role in feeding the stream (Figure ). The baseflow index (Qb/Qt), calculated using the annual mean discharge values, ranged from 88% to 96% between 2003 and 2014.…”
Section: Resultsmentioning
confidence: 96%
“…These results suggest that recharge tends to decrease with the increase in vadose zone thickness and vegetation density (grassland to woodland). Several authors have reported that land use and land cover have a strong influence on the groundwater recharge (Jobbágy & Jackson, ; Scanlon et al, ; Scott et al, ; Lucas et al, ); however, this is the first report regarding the influence of different cerrado physiognomies on recharge rates.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the IES site has similar hydrogeological characteristics (geology, and soil texture and structure) as the Onça Creek basin, we used a mean specific yield value of 12% (Wendland et al, ). As there are uncertainties in the recharge estimate by the WTF method, associated mainly with uncertainty in the Sy values (Coes, Spruill, & Thomasson, ), we applied an uncertainty factor of ±24% in recharge estimates according to results from a previous study conducted in the Onça Creek basin (Lucas et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation